Supply chain operations with online platform: Impacts of online reviews and manufacturer competition. (February 2023) - Shi, Song; Liu, Guilin
Highlights: Online reviews in a market would modify consumers' perceptions of quality. Impact of online reviews and manufacturer competition on supply chain decisions and profits. Different levels of online reviews that leads to different perceived product quality. Abstract: In an e-commerce market dominated by online platforms, as an important means of disseminating product information, online reviews play a significant role in influencing consumer-purchasing behavior. To study the influence of online reviews on supply chain decisions, this paper establishes a supply chain game composed of manufacturers and online platforms in a monopolistic market of manufacturers and a competitive market of manufacturers, respectively. In the monopolistic market of manufacturers, online reviews correct consumer-perceived quality. In the competitive market of manufacturers, online reviews correct consumer-perceived quality and then increase the level of competition between manufacturers. The results show that: (1) The influence of online reviews depends on the size of the value of online reviews. In the monopolistic market of manufacturers, the value of online reviews, if high enough, increases the profit and demand of the supply chain. On the other hand, a sufficiently small value of online reviews reduces the profit and demand of the supply chain. Whereas in the competitive market of manufacturers, online reviews change the level of competition. The manufacturer makes a profit only if the value of his online review is sufficiently higher than that of his competitor. For the online platform, online reviews will always increase her profit as long as the values of online reviews of both products are not too small at the same time. (2) Without online reviews, competition between manufacturers reduces the profit of the incumbent manufacturer. With online reviews, competition between manufacturers reduces the profit of the incumbent manufacturer while increasing the supply chain's total profit and the online platform's profit.